Social Responsibility and The Development of The Human Element: A Descriptive Study on A Sample of Beneficiaries of Social Responsibility Programs at The Royal Commission in Yanbu - Abu Shurayyan, Suhayb Mousa (Journal of Humanities & Social Sciences, 2023)
The current study aims to identify the role played by the social responsibility programs provided by the Royal Commission in Yanbu towards the development of the human element represented by the beneficiaries of those programs, as a group of sub-goals emerges from that main objective represented in identifying the developmental contributions of the social responsibility programs provided by the Royal Commission In Yanbu towards the beneficiaries of those programs and identifying the target community groups for social responsibility programs provided by the Royal Commission in Yanbu, in addition to revealing the dimensions of social responsibility that have been taken into account in the social responsibility programs provided by the Royal Commission in Yanbu, and finally providing suggestions that contribute to strengthening the role of social responsibility of the Royal Commission It stems towards the development of the human element, as the current study belongs to the descriptive studies that used the (specialized) social survey approach in terms of the subject of the research (and in-kind) in terms of the research community, as it is the most appropriate approach to the nature of the study, known as the “in-depth approach, in which the researcher describes phenomena and problems This approach is not limited to collecting information related to the subject of the study, but rather goes beyond that to analysis, interpretation and discovery of relationships, leading to conclusions that enrich the subject. (Al-Assaf, 2006). The most prominent results of the current study indicated the positive role of the social responsibility programs provided by the Royal Commission in Yanbu towards the beneficiaries of its employees and the residents of Yanbu Industrial City (the geographical scope of the Royal Commission in Yanbu).